Maximizing concentrated solar power (CSP) plant overall efficiencies by using spectral selective absorbers at optimal operation temperatures. (October 2015) - Burlafinger, Klaus; Vetter, Andreas; Brabec, Christoph J.
Highlights: Investigation of selective CSP absorbers compared to black bodies/common materials. Selective CSP absorbers can provide about 35% gain in plant efficiency. Providing a guideline for optimal optical properties for C  = 10–2000. Assuming realistic absorber properties λcut should be around 2.4 μm. Theoretical efficiency of an ideal CSP plant was calculated to up to ∼73%. Abstract: Selective absorbers for CSP plants to suppress thermal losses and to increase the efficiency is a promising topic and strong scientific efforts have been spent on how to design and realize such materials. However, there has been no comprehensive optimization analysis of the overall efficiency of CSP plants with selective absorbers. We performed a comprehensive computational parameter study of operation temperature and optical properties of the absorber and investigated their effect on the overall plant efficiency in dependence of sun light concentration up to C  = 2000 suns. Optimal operation temperatures were shown not to exceed 1383 K. By using selective absorbers instead of a black body or currently used materials, our assessment yields a potential electrical power output gain of up to around 35%. Our investigations also provide the optical parameters of an ideal (perfect selective) absorber. Its optimal cut off wavelength λcut lies around 2.4 μm for concentration factors below 120 and above 600 suns. For C in the range of 120–600 suns the value of the cut off wavelength is 1.79 μm. Simulating non-ideal (realistic) absorption properties, it was found that the strongest influence is caused by high absorption at low wavelengths. Low emittance at longer wavelengths plays a less important role. Also the sharpness of the transition from high absorption to low emittance plays a minor role regarding overall plant efficiency. As a rule of thumb, the cut-off wavelength should be at around 2.4 μm when assuming realistic (non-ideal) spectral selectivity. Finally, the theoretical maximum overall efficiency of a CSP plant achievable by an ideal selective absorber was calculated to up to 73% at 2000 suns and even up to 65% for a selective absorber with realistic optical properties.